Yeats and English Renaissance Literature - Chapman, Wayne K. author. aut Link
XX, 308 p.
Keywords: This book is the first to make extensive use of unpublished manuscripts to show how a period of English literature affected W.B.Yeats's development as a poet. Besides presenting a factual account of his acquaintance with English Renaissance writers based on evidence from his library and elsewhere, the study examines his response to numerous minor figures and several major ones - including Spenser, Jonson, Shakespeare, Donne and Milton.